(untitled) (Global Journal of Human-Social Science, 2019)
In this article the chronic genre is studied, seeking to analyze its formation and constitution as it was in Brazil. Taking as an analytical model undertaken for the understanding of the Brazilian romance formation, the method undertaken is dialectical and materialistic. The objective is to understand the formal constitution of the chronicle in its intimate relation with the formation of the Brazilian society of the century. XIX, that surrounds it. The series Bullets of pop is understood as a privileged exemplary of chronic production to undertake this analysis, given its characteristics and specific production conditions.